A SEMIOTICS ANALYSIS OF A-VOLUTION CIGARETTE TV ADVERTISEMENT - Assila Prianggi Humara Baiin, - (2011)
As a controversial commodity, cigarette has become exciting endless debates up to now, especially concerning the tar and nicotine of cigarette that can be lethal. By this controversy, cigarette advertisements in Indonesia are prohibited to present directly both the real form of cigarette and the activity of smoking. Therefore cigarette advertisements often use various images which represent the product including the image of masculinity. This research paper is aimed at finding out the textual codes and the significations of masculinity on A-volution cigarette TV advertisement. This study is focused on the analysis of connotative meaning of the textual codes and the semiotics analysis of narrations and moving pictures within signification process (semiosis) from Peirce. The method that is used in this study is qualitative analysis which is employed to obtain systematic, factual, and accurate data. The data consist of eleven scenes and four narrations which emphasize men values. The data are analyzed within the framework of textual codes and triadic sign relationship which are aimed to find the connotative meaning of masculinity. The findings reveal five elements of the textual codes and eleven significations of masculinity on the A-volution cigarette TV advertisement. The strong relation between the cigarette advertisement and the men values are evidenced within the textual codes and the significations which deal with the elements of the advertisement that are languages, pictures, and music. For further study, it is suggested to combine the theory of semiotics with gender and mass media theory. These theories do not only provide the meaning making production of connotative meaning but also the construction of a social context of the text in detail.